We love to craft Christmas : fun stuff for kids--17 handmade fabric & paper projects - Wrigley, Annabel, 1972- (FunStitch Studio, an imprint of C&T Publishing, 2015)
Provides instructions for Christmas-themed craft projects, including a festive holiday crown, woodland mushroom wreath, and a peaceful dove pincushion.